Pemenuhan Hak Nafkah Anak Pasca Perceraian: Studi Kasus Di Desa Banyuurip Gresik - Fitria Tahta Alfina (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
Livelihood is an obligation that must be fulfilled by the husband towards his wife and children. Livelihood can be in the form of birth income such as clothing, food, shelter and mental livelihood such as good moral teaching. Even if there is a divorce between husband and wife, the obligation to provide for children is still continuously fulfilled by the father. But in reality, in the community these income obligations tend to be neglected. Of course, this is not in line with what is in the Compilation of Islamic Law and Human Rights Instruments both nationally and internationally. This study aims to determine how the implementation of the fulfillment of children's support rights after divorce in Banyuurip Gresik Village. This research is empirical research with a sociological approach. Primary data in this study were secondary data obtained by the author through books, legal rules, journals, and previous research in accordance with the theme of this study. The data obtained is then analyzed through the stages of data preparation, data reduction, and conclusions. The results of this study show that the implementation of the fulfillment of children's support rights after divorce is not carried out properly. This is influenced by several factors, including no claim for income, inadequate economic conditions, and the absence of awareness and responsibility of the husband for the obligation to provide for children after divorce. Husbands tend to neglect these obligations and the fulfillment of children's support tends to be carried out by wives and their families.